EFL STUDENTS’ PERSPECTIVES TOWARDS THE USE OF ICT FOR SELF-REGULATION - Phuong, Vu Viet; Ha, Nguyen Thu; Tieu Yen, Do Thi; Thanh Ha, Nguyen Thi (VNU Journal of Foreign Studies, 2022)
This survey research aims to examine EFL students’ perceptions of using ICT to self-regulate their language learning. A total of 164 non-English majored sophomores at a public university completed a 25-item questionnaire which consisted of six areas regarding goal setting, resources, affection, cultural outcomes, metacognition monitoring, and social connection. The findings indicate participants utilized ICT to manage those aspects of their language learning. In addition, students were excited about using ICT devices to attain objects, control emotions, and manage resources, but less enthusiastic about using technology to engage in social learning and metacognitive monitoring. Several pedagogical implications have been recommended for pedagogists to stimulate students’ self-regulation in their language learning.